Moderasi Kehidupan Beragama dalam Tinjauan Tafsir Izwaji - Musthofa Musthofa (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
Moderation of religious life is a model of religious life which is based on the attitude of the soul that is in the midst of humility, considering maslahah and mahdarat towards a safe and peaceful life. Moderation of religious life can be built in four ways: (1) Knowledge, giving knowledge and understanding of how to live moderately in their environment (2) Fair, in the middle position in a religious life, not extreme, divided into fair which means honest, fair which means straight and fair which means sincere, (3) Tasamuh, which is a big heart accepting differences that may not be in accordance with his views, (4) Tawadlu, namely the attitude of a humble soul without appearing arrogant. This article is discussed through the Tafsir Izwaji approach, namely explanations in the form of information obtained from the Al-Quran, Al-Hadith and the opinions of Ulama or experts who are adequate.